Mitochondrial metabolism and the control of vascular smooth muscle cell proliferation - Chiong, Mario; Cartes-Saavedra, Benjamín; Norambuena-Soto, Ignacio; Mondaca-Ruff, David; Morales, Pablo E.; García-Miguel, Marina; Mellado, Rosemarie (Frontiers in Cell and Developmental Biology, 2014)
Differentiation and dedifferentiation of vascular smooth muscle cells (VSMCs) are essential processes of vascular development. VSMC have biosynthetic, proliferative, and contractile roles in the vessel wall. Alterations in the differentiated state of the VSMC play a critical role in the pathogenesis of a variety of cardiovascular diseases, including atherosclerosis, hypertension, and vascular stenosis. This review provides an overview of the current state of knowledge of molecular mechanisms involved in the control of VSMC proliferation, with particular focus on mitochondrial metabolism. Mitochondrial activity can be controlled by regulating mitochondrial dynamics, i.e., mitochondrial fusion and fission, and by regulating mitochondrial calcium handling through the interaction with the endoplasmic reticulum (ER). Alterations in both VSMC proliferation and mitochondrial function can be triggered by dysregulation of mitofusin-2, a small GTPase associated with mitochondrial fusion and mitochondrial–ER interaction. Several lines of evidence highlight the relevance of mitochondrial metabolism in the control of VSMC proliferation, indicating a new area to be explored in the treatment of vascular diseases.